2004
DOI: 10.1128/aem.70.12.7303-7310.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Characterization of Propionicin F, a Bacteriocin fromPropionibacterium freudenreichii

Abstract: This work describes the purification and characterization of propionicin F, the first bacteriocin isolated from Propionibacterium freudenreichii. The bacteriocin has a bactericidal activity and is only active against strains of P. freudenreichii. Propionicin F appears to be formed through a processing pathway new to bacteriocins. The mass of the purified bacteriocin was determined by mass spectrometry, and the N-terminal amino acid sequence was determined by Edman degradation. Sequencing of pcfA, the bacterioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…TrnC exhibited sequence similarity to conserved domains of the Fe-S oxidoreductase arylsulfatase regulatory proteins (AslB), and TrnD had sequences similar to the MoaA family of molybdenum cofactor enzymes. Radical SAM enzymes rarely occur in bacteriocin gene clusters, but they are included in those of subtilosin A and propiocin F (26,27). Sequence alignments indicated that AlbA of subtilosin A exhibits only 19% and 17% identity to TrnC and TrnD, respectively, although AlbA exhibits some features of each individual thuricin CD protein.…”
Section: Resultsmentioning
confidence: 99%
“…TrnC exhibited sequence similarity to conserved domains of the Fe-S oxidoreductase arylsulfatase regulatory proteins (AslB), and TrnD had sequences similar to the MoaA family of molybdenum cofactor enzymes. Radical SAM enzymes rarely occur in bacteriocin gene clusters, but they are included in those of subtilosin A and propiocin F (26,27). Sequence alignments indicated that AlbA of subtilosin A exhibits only 19% and 17% identity to TrnC and TrnD, respectively, although AlbA exhibits some features of each individual thuricin CD protein.…”
Section: Resultsmentioning
confidence: 99%
“…Among them it could be mentioned: Propionicin PLG-1 and GBZ-1 produced by P. thoenii 127 [81]; Jenseniin G isolated from P. thoenii P126 [82]; Propionicins SM1 and SM2 produced by P. jensenii DF1 [83]; Propionicin T1 synthesized by P. thoenii 419 and LMG2792 [84]; Thoenicin 447 isolated from P. thoenii 447 [85]; Acnecin produced by a strain of P. acnes [86] and several other propionicins [87][88][89].…”
Section: Antimicrobials Production: Propionic Acid and Bacteriocinsmentioning
confidence: 99%
“…Electroporation of competent P. freudenreichii subsp. shermanii IFO12426 cells produced 10 4 and Ͼ10 7 transformants/g DNA with vector prepared from E. coli and P. freudenreichii, respectively. With DNA from E. coli, this is an improvement in transformation efficiency by 3 orders magnitude compared to the transformation of P. freudenreichii ATCC 6207.…”
Section: Resultsmentioning
confidence: 99%
“…PAB also have a potential use as protective cultures for inhibition of pathogens and food spoilage organisms (30,31). The antimicrobial capacity of PAB is only partly due to the production of organic acids, and it has become evident that PAB also produce other biologically active substances such as bacteriocins (4,7,9,13,26). Recently, Faye et al (9) characterized the propionicin T1 bacteriocin from Propionibacterium thoenii.…”
mentioning
confidence: 99%